CREATING PRODUCT CREATIVITY TO OBTAIN PRODUCT DIFFERENTIATION IN ORDER TO IMPROVE THE MARKETING PERFORMANCE OF RATTAN PRODUCTS (International Journal of Innovative Technologies in Economy, 2024)
The increasing diversity and attractiveness of rattan products have intensified competition in the rattan industry, both domestically and internationally. This has led to a situation where the global impact of rattan trade is largely dominated by countries such as China, Taiwan, and Europe, in addition to Indonesia. The main objective of this research is to explore how product creativity affects product differentiation, ultimately enhancing the marketing performance of rattan products in Cirebon Regency. The study focused on all rattan business actors in the region, with a sample size of 210 respondents selected using Hair's formula. The data collection method involved a questionnaire and Probability Sampling technique. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEMPLS). The findings revealed that Product Differentiation has a more significant impact on Marketing Performance compared to Product Creativity. This is because consumers are inclined towards unique products with distinct characteristics offered by companies.